What matters for drug delivery to tumor by nanoparticles: Gaining insights from PBPK/PD simulation of drug nanocrystals - Shan Lu; Clairissa Corpstein; Kinam Park; Tonglei Li (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: In our previous studies, drug nanocrystals were directly prepared by solution crystallization, possessing uniform particle size and morphology suitable for intravenous (IV) injection. These nanocrystals accumulated in a small percentage of their injected dose in tumor-bearing mice but showed similar anti-tumor effectiveness and much-reduced side effects compared with current commercial solubilized and encapsulated delivery systems. Experimental approach: In this study, we aimed to delineate possible controlling factors for the pharmacokinetics (PK) and biodistribution behaviors of paclitaxel (PTX) nanocrystals tested in mice by applying physiologically based pharmacokinetics (PBPK) modeling, coupled with pharmacodynamics (PD) simulation, to the data. Key Results: Our results show that clearance of the drug plays a significant, if not the most important, role in determining tissue distribution, including tumor accumulation of PTX nanocrystals. Surface treatment of drug nanocrystals with polymeric surfactants also appeared to affect PK profiles and PD outcomes. Importantly, when scaled to model human parameters, our PK/PD simulations suggest that drug distribution in humans, as opposed to animal models, was significantly influenced by tissue partitioning rather than drug clearance. This finding could facilitate the design and development of future drug delivery systems. Conclusion: Drug nanocrystals deposited in tissues, including tumors, could therefore act as depots, releasing the drug back into the circulation, possibly contributing to extended treatment, as well as any detrimental effects.